Comparative analysis between digital PCR and blood culture for blood pathogen detection - Zhao, Min; Yang, Yan; Yao, Lifeng; Chen, Huiming; Zhang, Mengqing; Guo, Yaozhen; Zhang, Sichao; Huang, Rong; Cai, Fengrong; Zhang, Ling (Frontiers in Medicine, 2025)
IntroductionRapid and accurate identification of pathogens causing blood infections plays a pivotal role in the early diagnosis and management of infections. Digital PCR (dPCR) is a new nucleic acid amplification technology exhibiting high sensitivity for the rapid detection and absolute quantification of multiple pathogens in the blood.MethodsHerein, we conducted a retrospective study involving 149 patients with suspected infections and compared the differences between dPCR assay and blood culture in pathogen detection.ResultsBlood culture showed six positive specimens and six pathogenic strains, whereas dPCR assay showed 42 positive specimens and 63 pathogenic strains. The concentrations of positive pathogens detected via dPCR varied from 25.5 to 439,900 copies/mL.DiscussionOur study demonstrated that dPCR assay has higher sensitivity, shorter detection time, and wider detection range than blood culture in blood pathogen detection, indicating its capability to support anti-infective therapy for patients.